2003
DOI: 10.6090/jarq.37.195
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Estrogen Concentrations during the First Trimester of Gestation in Dairy Cows: Comparison with the Origin of Embryos and Fetal Number

Abstract: The objectives of this study were to determine the profiles of plasma estrogen concentrations during the first trimester of gestation and to correlate them with the origin of the embryos and fetal number. Pregnancies were induced either by artificial insemination (AI) on the day of estrus (day 0) or by transfer of 1 or 2 blastocysts produced in vitro (IVF-ET) on day 7. Five singleton-bearing cows impregnated by AI, and 6 singleton and 6 twin pregnancies induced by IVF-ET were used in the experiment. Blood was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Similarly, Opara et al (2006) reported higher level of estradiol in pregnant heifers as compared to estrus or other reproductive conditions (anestrus or diestrus) and in this situation findings of present study are in agreement with these earlier reports. Hirako et al (2003) reported that during the 1 st trimester of gestating cows, E2-17β remained at basal levels until day 80, followed by an increase in estrone and E217β after day 80 of gestation. Also, Al-Anbaky ( 2009) suggested that in pregnant cow's plasma E2 -17β levels varied from 9 pg/ml (in the first third of pregnancy) to 282.60 pg/ml (during the last month of gestation).Similar findings were reported by El-Masry et al…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Opara et al (2006) reported higher level of estradiol in pregnant heifers as compared to estrus or other reproductive conditions (anestrus or diestrus) and in this situation findings of present study are in agreement with these earlier reports. Hirako et al (2003) reported that during the 1 st trimester of gestating cows, E2-17β remained at basal levels until day 80, followed by an increase in estrone and E217β after day 80 of gestation. Also, Al-Anbaky ( 2009) suggested that in pregnant cow's plasma E2 -17β levels varied from 9 pg/ml (in the first third of pregnancy) to 282.60 pg/ml (during the last month of gestation).Similar findings were reported by El-Masry et al…”
Section: Resultsmentioning
confidence: 99%
“…Several potential mechanisms affect the level of E2-17β during the pregnancy period, whereas the concentration of fetal cortisol from fetal adrenals helps in E2-17β releases from placenta (Gitau et al, 2005). Further, the conversion of testosterone hormone into E2-17β held at the granulosa cells by the action of aromatase (Peters & Ball, 1995;Hirako et al 2003). Also, sex of fetus and the levels of progesterone hormone might also associate with the releases -17β (EL-Fouly et al, 1998 b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation